The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/cbin.12029
|View full text |Cite
|
Sign up to set email alerts
|

Promising applications of red cell distribution width in diagnosis and prognosis of diseases with or without disordered iron metabolism

Abstract: Many indicators, including red cell distribution width (RDW) and iron metabolism, are sensitive to a variety of risk factors, and are associated with the pathological alterations and disease onset. RDW reflects the degree of heterogeneous volumes of peripheral red blood cells (RBCs). It has been well‐known that increased RDW indicates iron deficiency anemia, hemolytic anemia, ineffective erythropoiesis, and shorten lifespan of RBCs. Increased RDW is also prevalent in various non‐anemic pathological conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…6,7 Numerous studies have demonstrated that RDW is associated with aging, inflammation, oxidative stress, nutritional deficiency, erythropoiesis impairment, and telomere shortening. [8][9][10][11] To date, increasing evidence has shown that RDW is associated with worse outcomes in many diseases, including acute exacerbation of chronic obstructive pulmonary disease, COVID-19, multiple myeloma, heart failure, spontaneous intracerebral hemorrhage, and community-acquired pneumonia. [12][13][14][15][16][17] Recently, Deniz et al 18 revealed the significant predictive value of RDW in mortality among ICU patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Numerous studies have demonstrated that RDW is associated with aging, inflammation, oxidative stress, nutritional deficiency, erythropoiesis impairment, and telomere shortening. [8][9][10][11] To date, increasing evidence has shown that RDW is associated with worse outcomes in many diseases, including acute exacerbation of chronic obstructive pulmonary disease, COVID-19, multiple myeloma, heart failure, spontaneous intracerebral hemorrhage, and community-acquired pneumonia. [12][13][14][15][16][17] Recently, Deniz et al 18 revealed the significant predictive value of RDW in mortality among ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…tion can disrupt iron metabolism, impair erythropoietin (EPO) production, and hinder RBC maturation, resulting in elevated RDW values 11. Moreover, oxidative stress and hypoxia have been implicated in abnormal RDW levels.…”
mentioning
confidence: 99%